Modelling and optimisation of treatment parameters using response surface methodology: application to superficial hardening of 2017A alloy using the rods-balls device. (2018) - Amrou, M.H.E.; Hamouda, K.; Keddam, M.
This work was concerned with the study of the surface hardening process of 2017A alloy using the rods-balls device. The objective of this work was to define the optimal processing parameters relative to the surface hardness of 2017A alloy using the response surface methodology. The regression model proposed in this paper has been developed using the central composite design (CCD). Analysis of variance (ANOVA) was validated with a confidence level > 93%. The final model is established on the basis of additional statistical analysis using other statistical criteria such as Malows cp and Akaike's information criterion. The optimal point (d = 4 mm, t = 10 min and f = 50 Hz) was determined by the Hessian matrix, it corresponded to the highest surface hardness value Hs = 422.25 HB. Highest surface hardness is then characterised by a gain in hardness Hs of 35.68%.